ANALISIS HUMAN REABILITY DAN PERBAIKAN PROSES PENGOLAHAN GULA RAFINASI - Hartomo Hartomo; Asih Setyorini (Journal of Industrial Engineering Management, 2019)
In Indonesia sugar needs is very significant along with the population, food and beverage industries, so the sugar industry is required to provide quality products. Determination of standardization of sugar quality in processing is influecend by machine conditions and human reability. This studyaims to analyze human error inrefiend sugar processing and determine recommedations for improvements neede to improve human reability in refined sugar processing. The methodused in this study is the Human Error Assesment and Reduction Techiue (HEART) and Human Error Reduction and Prediction Approach (SHERPA)which can calculate and provide solutions to the probability of the occurrence of errors. The results of this study indicate that the total human reability value of refined sugar processing is 5,34891 and there are 4 improvenebt strategies, such as undertake briefing, make records by making checklist form and making display poster about cleanliness